Preparing teachers to teach with technology - Vrasidas, Charalambos; Glass, Gene V., 1940- (Current perspectives on applied information technologies., 2005)
Teacher preparation programs in the United States and around the world have finally begun to address this deficiency in their programs. The realization that technology is a powerful driving force in education coupled with a renewed emphasis on teacher preparation by governments have resulted in some dramatic changes in teacher preparation programs. I believe that we have just begun to see changes in teacher preparation and that the pace of change will continue to accelerate. This volume covers some of the more exciting developments in the field, including the emergence of wireless computing in the classroom and the preparation of teachers in an online environment. In short, I am optimistic. For those of you who are also in the field, I think you will agree. For those who are just entering the field, this book is a great place to start as you change education. Finally, while this book is the last book of the three part series that we at CAIT conceptualized with Charalambos Vrasidas and Gene Glass, it is also the beginning of a new relationship. We are excited to join with a new partner, CARDET, to present this book. Over many years in the education and R&D field, I have come to realize the value of partnerships and relationships. I want to thank both Charalambos and Gene for making this series a reality and such a success. We are looking forward to working with them and CARDET in the near future.